Arthritis and coeliac disease. Issue 9 (September 1985) - Bourne, J T; Kumar, P; Huskisson, E C; Mageed, R; Unsworth, D J; Wojtulewski, J A
Abstract : We report six patients with coeliac disease in whom arthritis was prominent at diagnosis and who improved with dietary therapy. Joint pain preceded diagnosis by up to three years in five patients and 15 years in one patient. Joints most commonly involved were lumbar spine, hips, and knees (four cases). In three cases there were no bowel symptoms. All were seronegative. X-rays were abnormal in two cases. HLA-type A1, B8, DR3 was present in five and B27 in two patients. Circulating immune complexes showed no consistent pattern before or after treatment. Coeliac disease was diagnosed in all patients by jejunal biopsy, and joint symptoms in all responded to a gluten-free diet. Gluten challenge (for up to three weeks) failed to provoke arthritis in three patients tested. In a separate study of 160 treated coeliac patients attending regular follow up no arthritis attributable to coeliac disease and no ankylosing spondylitis was identified, though in a control group of 100 patients with Crohn's disease the expected incidence of seronegative polyarthritis (23%) and ankylosing spondylitis (5%) was found (p less than 0.01). Arthritis appears to be a rare manifestation of coeliac disease. This relationship may provide important clues to the role of gastrointestinal antigens in rheumatic diseases.